Novel Score for Stratifying Risk of Critical Care Needs in Patients With Intracerebral Hemorrhage - Faigle, Roland (Neurology, 2021)
OBJECTIVE: To develop a risk prediction score identifying patients with intracerebral hemorrhage (ICH) at low risk for critical care. METHODS: We retrospectively analyzed data of 451 patients with ICH between 2010 and 2018. The sample was randomly divided into a development and a validation cohort. Logistic regression was used to develop a risk score by weighting independent predictors of intensive care unit (ICU) needs according to strength of association. The risk score was tested in the validation cohort and externally validated in a dataset from another institution. RESULTS: The rate of ICU interventions was 80.3%. Systolic blood pressure (SBP), Glasgow Coma Scale (GCS) score, intraventricular hemorrhage (IVH), and ICH volume were independent predictors of critical care, resulting in the following point assignments for the Intensive Care Triaging in Spontaneous Intracerebral Hemorrhage (INTRINSIC) score: SBP 160 to 190 mm Hg (1 point), SBP >190 mm Hg (3 points); GCS 8 to 13 (1 point), GCS <8 (3 points); ICH volume 16 to 40 cm(3) (1 point), ICH volume >40 cm(3) (2 points); and presence of IVH (1 point), with values ranging between 0 and 9. Among patients with a score of 0 and no ICU needs during their emergency department stay, 93.6% remained without critical care needs. In an external validation cohort of patients with ICH, the INTRINSIC score achieved an area under the receiver operating characteristic curve of 0.823 (95% confidence interval 0.782–0.863). A score <2 predicted the absence of critical care needs with 48.5% sensitivity and 88.5% specificity, and a score <3 predicted the absence of critical care needs with 61.7% sensitivity and 83.0% specificity. CONCLUSION: The INTRINSIC score identifies patients with ICH who are at low risk for critical care interventions. CLASSIFICATION OF EVIDENCE: This study provides Class II evidence that the INTRINSIC score identifies patients with ICH at low risk for critical care interventions.